PENGETAHUAN KELUARGA TENTANG PENCEGAHAN PENYAKIT MALARIA - Azlan Suwanda; Sri Legawati (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Malaria is a disease caused by protozoa of the genus Plasmodium. Malaria in humans can be caused by P. malariae, P. vivax, P. falciparum, and P. ovale. Malaria is transmitted by female Anopheles mosquitoes, resulting in infection of red blood cells by Plasmodium, which is transmitted through the Anopheles mosquito's bloodsucking. The purpose of this study was to determine family knowledge about malaria prevention. This study used a descriptive survey design with a cross-sectional approach. The study population was 103 heads of families in Darussalam Hamlet, Teluk Piai Village, with a sample of 20 respondents. Respondents were family members suffering from malaria. The sample was selected using the Probability  sampling technique or Simple Random Sampling, where the sample was drawn randomly without regard to strata within the population. Based on the results, it was found that family knowledge about malaria prevention was categorized as quite good, with a score of 6.75 (67.5%). Although families understand the basic transmission methods, there are still shortcomings in the technical aspects of independent primary prevention. Conclusion: Family knowledge is at a moderate (sufficient) level. Strengthening health education through a family-centered approach is needed to increase understanding and shift preventive behavior from adequate to good to support the malaria elimination program.